Identifikasi Karakteristik Masjid Kuno Indonesia Pada Masjid Tuha Gunong Kleng Aceh Barat - Alfikhairina Jamil (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
Mosques are works of Islamic architecture that are closest to our everyday life. Masjid Tuha Gunong Kleng is located in West Aceh, and is one of the mosques that can represent the development of ancient Indonesian mosque architecture from time to time. Visually, Masjid Tuha Gunong Kleng shows many similarities with other ancient mosques in Indonesia. Eventhough Masjid Tuha Gunong Kleng has been designated as a cultural heritage site by the Aceh Cultural Heritage Conservation Center, in-depth studies about Masjid Tuha Gunong Kleng is still difficult to get, both from either architectural or historical perspective.